2019
DOI: 10.1186/s40658-019-0247-x
|View full text |Cite
|
Sign up to set email alerts
|

NEMA NU 2–2007 performance characteristics of GE Signa integrated PET/MR for different PET isotopes

Abstract: Background Fully integrated PET/MR systems are being used frequently in clinical research and routine. National Electrical Manufacturers Association (NEMA) characterization of these systems is generally done with 18 F which is clinically the most relevant PET isotope. However, other PET isotopes, such as 68 Ga and 90 Y, are gaining clinical importance as they are of specific interest for oncological applications and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 32 publications
(39 reference statements)
4
39
0
Order By: Relevance
“…This dependency is clearly demonstrated at the interface between different tissues as shown in Figure 6. These findings are in agreement with previous studies on the positron range (Rickey et al, 1992;Cal-González et al, 2009;Shah et al, 2014;Alva-Sánchez et al, 2016;Huang et al, 2016;Caribé et al, 2017), and confirm a reduced positron range in the perpendicular direction of a magnetic field. Moreover, studies have also indicated (Iida et al, 1986;Wirrwar et al, 1997;Soultanidis et al, 2011;Kraus et al, 2012) that a higher magnetic field will also induce a greater reduction of the positron range.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This dependency is clearly demonstrated at the interface between different tissues as shown in Figure 6. These findings are in agreement with previous studies on the positron range (Rickey et al, 1992;Cal-González et al, 2009;Shah et al, 2014;Alva-Sánchez et al, 2016;Huang et al, 2016;Caribé et al, 2017), and confirm a reduced positron range in the perpendicular direction of a magnetic field. Moreover, studies have also indicated (Iida et al, 1986;Wirrwar et al, 1997;Soultanidis et al, 2011;Kraus et al, 2012) that a higher magnetic field will also induce a greater reduction of the positron range.…”
Section: Discussionsupporting
confidence: 93%
“…In this work we have developed and evaluated a model for the GE Signa PET/MR to run realistic Monte Carlo simulations using GATE. The model was validated by comparing simulated sensitivity and NECR data 18 F and 68 Ga with corresponding measurements performed on a GE Signa PET/MR system (Caribé et al, 2019). Once validated, these simulations allowed us to evaluate the system characteristics in terms of sensitivity and NECR for different, less conventional PET isotopes such as 15 O, 13 N, 11 C, and 82 Rb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At higher activities, detector saturation effects can start to paralyze the system and reduce performance such that the count rate is no longer linear with increasing activity. At low activities and in the normal clinical range, the true and scatter coincidences scale roughly linear with the activity (within limits), while the randoms scale more like a quadratic function (actual curves can be found in [31]). In a real low-dose PET scan, the amount of randoms is therefore likely lower than in our simulated low-dose PET.…”
Section: Discussionmentioning
confidence: 79%